Design and development of a stand-alone multi-level inverter for photovoltaic (PV) application - Salam, Zainal (Faculty of Electrical Engineering, 2003)
Multilevel voltage source inverter (VSI) has been recognized to be very attractive in high voltage dc to ac conversion. It offers several advantages compared to the conventional two-level inverter, namely reduced switching losses and better harmonic performance. This work proposed a new switching strategy for a particular multilevel topology, known as the modular structured multilevel inverter (MSMI). The proposed scheme is based on symmetric regular sampled unipolar PWM technique. Unlike other techniques proposed by other researchers, this method uses multiple modulating waveform with a single carrier. Mathematical equations that define the PWM switching instants is derived. The derived equations are verified by computer simulation. To justify the merits of the proposed modulation scheme, prediction on the output voltage harmonics using Fourier analysis is carried out. An experimental five-level MSMI test-rig is built to implement the proposed algorithm. Using this set-up, it was found that the derived equations could be easily implemented by a low-cost fixed-point microcontroller. Several tests to quantify the performance of the inverter under the proposed modulation scheme is carried out. The results obtained from these tests agree well with theoretical prediction.